Answer:
816 cm²
Step-by-step explanation:
Surface area of the composite figure = (surface area of the larger rectangular prism + surface area of the smaller rectangular prism) - area of the side of the smaller rectangular prism that is joined to the bigger prism.
✔️Surface area of the larger rectangular prism:
Area = L*W*H = 20*5*6 = 600 cm²
✔️surface area of the smaller rectangular prism:
Area = L*W*H = 12*4*6 = 288 cm²
✔️area of the side of the smaller rectangular prism that is joined to the bigger prism.
Area = L*W = 12*6 = 72 cm²
Surface area of the composite = (600 + 288) - 72 = 888 - 72 = 816 cm².
Answer:
1.6
Step-by-step explanation:
4.4 - 2.8 = 1.6
6 - 4.4 = 1.6
7.6 - 6 = 1.6
The equivalence of the equation is 5x + 48 = 5x + 3.
Since 48 cannot be equal to 3, hence there are no solution.
<h3>What is the value of x?</h3>
Given the equation; x-4[ x - 2( x + 6) ] = 5x + 3
We remove the parentheses
x-4[ x - 2( x + 6) ] = 5x + 3
x-4[ x - 2x - 12 ] = 5x + 3
x - 4x + 8x + 48 = 5x + 3
5x + 48 = 5x + 3
We can go further and collect like terms
5x - 5x + 48 = 3
48 ≠ 3
Since 48 cannot be equal to 3, hence there are no solution.
Learn more about equations here: brainly.com/question/14686792
#SPJ1
Answer:
Step-by-step explanation:
f(-x) is a reflection of f(x) in the y-axis
Answer:
undefined
Step-by-step explanation:
The expression contains a division by
0
The expression is undefined.
Undefined